2020
DOI: 10.1007/s00429-020-02103-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct administration of ifenprodil and citalopram into the nucleus accumbens inhibits cue-induced nicotine seeking and associated glutamatergic plasticity

Abstract: Nicotine use disorder has been associated with glutamatergic alterations within the basal ganglia that might contribute to relapse. Specifically, initiation of cue-induced nicotine seeking produces rapid, transient synaptic potentiation (t-SP) in nucleus accumbens core (NAcore) medium spiny neurons (MSNs), defined as increases in spine head diameter and AMPA to NMDA current ratios (A/N). Ifenprodil, which inhibits nicotine reinstatement when administered systemically, antagonizes GluN2B-containing NMDA recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Repeated nicotine exposure increases the overall expression of the GluN2B subunits in the CPu, particularly on the membrane surface. Consistent with the present ndings, previous studies have demonstrated a correlation between synaptic GluN2B subunits and alterations in spine morphology of striatal neurons following exposure to cocaine or nicotine [37,49,51,52]. Rats in early withdrawal from cocaine self-administration increase excitatory inward ion currents that are mediated by stimulating the GluN2B subunits [31].…”
Section: Discussionsupporting
confidence: 92%
“…Repeated nicotine exposure increases the overall expression of the GluN2B subunits in the CPu, particularly on the membrane surface. Consistent with the present ndings, previous studies have demonstrated a correlation between synaptic GluN2B subunits and alterations in spine morphology of striatal neurons following exposure to cocaine or nicotine [37,49,51,52]. Rats in early withdrawal from cocaine self-administration increase excitatory inward ion currents that are mediated by stimulating the GluN2B subunits [31].…”
Section: Discussionsupporting
confidence: 92%
“…In experiment 1, animals were killed following nicotine self-administration and 4 d of hormone treatments. Rats were anesthetized with CO 2 and rapidly decapitated, similar to other studies using whole-cell electrophysiology ( Dubé et al, 2005 ; Spindle and Thomas, 2014 ; Leyrer-Jackson et al, 2020 ). Brains were removed and placed into ice-cold cutting solution (cutting aCSF) containing (in mmol/l): NaCl, 120; NaHCO 3, 25; dextrose, 10; KCl, 3.3; NaH 2 PO 4 , 1.23; CaCl 2 , 1.8; MgCl 2 , 2.4 and saturated with carbogen (95% O 2 /5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%